Analysis of Leading Commodities in the Livestock Sub-Sector and Development Direction in Semangga District, Merauke Regency (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
The purpose of this study is to provide information on the leading commodities in the livestock sub-sector and the direction of its development. This research is also expected to provide an overview of the priority scale for livestock business development. The method used in this research is descriptive method. This method is used to describe an object through data, namely the leading commodity in the livestock sub-sector in Semangga District, Merauke Regency. The determination of the location was determined deliberately based on the consideration that the majority of the people in Semangga District are transmigrants whose livelihoods are farmers and ranchers. While the respondents in this research were all breeders in the Semangga District. The data analysis used is Location Quotient (LQ) and Differential Shift (DS) analysis in Shift Share Analysis (SSA). LQ analysis is carried out in order to answer the leading commodities in the livestock sub-sector and SSA analysis is used to see the direction of business development in the livestock sub-sector. The main commodities of the livestock sub-sector in Semangga District are cattle, goats, native chickens, laying hens, and ducks. Cattle in Waninggap Nanggo, Matara, Sidomulyo, Semangga Jaya, Kuprik and Waninggap Kai Villages. The directions for the development of the livestock sub-sector in the Semangga District are cattle in Semangga Jaya Village, goats in Muram Sari Village, native chickens in Kuprik Village, laying hens in Sidomulyo Village and ducks in Waninggap Nanggo Village.